2013
DOI: 10.1007/s00253-013-5257-3
|View full text |Cite
|
Sign up to set email alerts
|

Virus-like particles produced in Saccharomyces cerevisiae elicit protective immunity against Coxsackievirus A16 in mice

Abstract: Hand, foot, and mouth disease (HFMD) has caused significant morbidity and mortality in the Asia-Pacific regions, particularly in infants and young children. Coxsackievirus A16 (CA16) represents one of the major causative agents for HFMD, and the development of a safe and effective vaccine preventing CA16 infections has become a public health priority. In this study, we have developed a yeast system for the production of virus-like particles (VLPs) for CA16 by co-expressing P1 and 3CD of CA16 in Saccharomyces c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…168 Virus-like particles (VLP) produced in Saccharomyces cervisiae have also elicited potent neutralizing responses and passive transfer of immune sera protected neonate mice against lethal CV-A16 challenge. 169 Combination of inactivated EV-A71/CV-A16 vaccines formulated in alum 170 or with PELC/CpG 171 elicited balanced neutralizing responses against both viruses whereas monovalent CV-A16 vaccines did not protect against EV-A71 infection. Furthermore, maternal immunization of mice with the bivalent vaccine protected neonates challenged with the mouse-adapted EV-A71/MVA-N strain and the clinical isolate CV-A16/G08.…”
Section: Development Of a Bivalent Ev-a71/cv-a16 Vaccinementioning
confidence: 99%
“…168 Virus-like particles (VLP) produced in Saccharomyces cervisiae have also elicited potent neutralizing responses and passive transfer of immune sera protected neonate mice against lethal CV-A16 challenge. 169 Combination of inactivated EV-A71/CV-A16 vaccines formulated in alum 170 or with PELC/CpG 171 elicited balanced neutralizing responses against both viruses whereas monovalent CV-A16 vaccines did not protect against EV-A71 infection. Furthermore, maternal immunization of mice with the bivalent vaccine protected neonates challenged with the mouse-adapted EV-A71/MVA-N strain and the clinical isolate CV-A16/G08.…”
Section: Development Of a Bivalent Ev-a71/cv-a16 Vaccinementioning
confidence: 99%
“…Currently, several experimental CVA16 and EV71 vaccines are under development, including inactivated CVA16, [23][24][25] and CVA16 VLPs derived from insect cells 26 and Saccharomyces cerevisiae. 27 Among these, the EV71 inactivated vaccine has been evaluated and passed through a phase III clinical trial, while the development of EV71 VLPs in insect cells and S. cerevisiae is still ongoing. 28,29 However, until now these vaccines have not been evaluated in bivalent composition.…”
Section: Introductionmentioning
confidence: 99%
“…Various candidates against EV71 or CA16 virus, including inactivated vaccines (3,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), live attenuated vaccines (23,24), subunit vaccines based on the VP1 protein (25), virus-like particle (VLP) vaccines (26)(27)(28)(29)(30)(31)(32)(33)(34), and epitopebased vaccines (35)(36)(37)(38)(39), were shown to possess various levels of efficacy in animal studies or human clinical trials. In particular, inactivated EV71 vaccines showed promising results against EV71-associated diseases in recent phase 3 clinical studies conducted in mainland China (20)(21)(22).…”
mentioning
confidence: 99%
“…Both EV71 and CA16 VLPs consist of 60 copies for each of the capsid proteins, VP0, VP1, and VP3, which follow a P ϭ 3 icosahedral arrangement. Previous studies showed that both EV71 and CA16 VLPs can elicit potent immune responses and are able to protect immunized mice against lethal challenges with EV71 or CA16 virus (27,31,33,34). How VLP vaccines mimic their viral counterparts structurally and how the neutralizing epitopes are preserved on the surface of VLPs are issues of big interest for effective vaccine development.…”
mentioning
confidence: 99%